#TITLE_ALTERNATIVE# - Pangihutan Adeltua (NIM 242 04 004), Harlan
Abstract : Increases in maintenance costs of toll roads, is often attributed to the overloading behavior of trucks. The premature damage of road surfaces due to excess loadaffluence would significantly affect the magnitude of maintenance costs. Unfortunately, the method for calculating road toll charge has not yet been able to accommodate the importance overloading behaviour. As a consequence, the current used fails to represent the traffic condition and behaviors comprehensively. The objective of this thesis is to develop a model of toll charge in association with vehicle classes which enables the accommodation of overloading condition as well as compares the new toll-charge model with the existing ones. A case study was held at the Tangerang-Merak Toll Road The data is collected from several institutions including PT Marga Mandala Sakti, PT Jasa Marga (Persero), Puslitbang Prasarana Transportasi and Badan Pusat Statistik. The analyses is conducted to describe the comparisons of without and with overloading situations. In the analyses, road tariff modeling was based on investment viability approach. Modification of this approach was done to develop tariff equation as a function of marginal of basic investment cost and marginal of additional investment cost impacted by overloading. Findings of the study include: (i) overloading behavior tend to be existed in vehicle class of 2 axle truck, 3-axle truck, trailer, traktor+2-axle semi trailer, and traktor+3 axle semi trailer, (ii) ESA Index for all vehicle types increase from 2,1150 to 2,7051. The difference of operation and maintenance costs between with and without situation became Rp 3.192.046. Meanwhile, the difference of investment costs between with and without situation became Rp 2.113.405. The equations for calculating tariff were obtained as follows: (1) Tarif for Category I = 0,3920*SBPI + 0,0145*SPBIADO, (2) Tarif for Category II A = 0,1026*SBPI + 0,3256*SPBIADO, (3) Tarif for Category II B = 0,5054*SBPI + 0,6599*SPBIADO.